Exploiting the amazing diversity of natural source-derived polysaccharides: Modern procedures of isolation, engineering, and optimization of antiviral activities - Ray, Bimalendu; Schütz, Martin; Mukherjee, Shuvam; Jana, Subrata; Ray, Sayani; Marschall, Manfred (Polymers, 2021)
Naturally occurring polysaccharide sulfates are highly diverse, owning variations in the backbone structure, linkage pattern and stereochemistry, branching diversity, sulfate content and positions of sulfate group(s). These structural characteristics bring about diverse sulfated polymers with dissimilar negative charge densities and structure–activity relationships. Herein, we start with a short discussion of techniques needed for extraction, purification, chemical sulfation, and structural characterization of polysaccharides. Processes of isolation and sulfation of plant-derived polysaccharides are challenging and usually involve two steps. In this context, we describe an integrated extraction-sulfation procedure that produces polysaccharide sulfates from natural products in one step, thereby generating additional pharmacological activities. Finally, we provide examples of the spectrum of natural source-derived polysaccharides possessing specific features of bioactiv-ity, in particular focusing on current aspects of antiviral drug development and drug–target inter-action. Thus, the review presents a detailed view on chemically engineered polysaccharides, espe-cially sulfated derivatives, and underlines their promising biomedical perspectives.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Amalgamated extraction-sulfation methods; Broad-spectrum bioactivity; Chemical profiles; Natural source-derived compounds; Polysaccharide sulfates; Specific antiviral activities; Structure–activity relationships